Extraction of Uronic Acid From Sargassum crassifolium and Its Feeding Effects On The Eggs Production and Quality of Lohmann Chicken Eggs - Veybe Gresje Kereh; Ivonne Maria Untu; Marie Najoan; T. Lumi (Universitas Halu Oleo, 2020)
ABSTRACTThe use of antibiotics in chicken feed is currently banned because it can cause resistance to pathogenic bacteria and cause residues in products. This study aimed to see the effect of drinking water containing uronic acid extracted from Sargassum crassifolium (S. crassifolium) on the physical and chemical quality of Lohmann chicken eggs. One hundred and twenty laying hens were divided into 2 groups: (1) chickens given commercial feed containing antibiotics and (2) feed without additional antibiotics. The chickens were randomly assigned to one of the 5 brown seaweed supplementation treatments in drinking water A1=0.0% S.crassifolium (control); A2=2.5% S.crassifolium; A3=5.0% S.crassifolium; A4=7.5% S.crassifolium; A5=10.0% S.crassifolium. The study used a completely randomized factorial design of 5 treatments, 2 factors, and 3 replications. Each replication consisted of 6 heads of laying hens. There were no differences between treatments on the performance of laying hens (egg production, egg weight, egg mass, feed conversion); physical quality (eggshell, egg yolk, egg white, shell thickness, egg yolk, Haugh unit, egg index) and chemistry (superoxide dismutase production, thiobarbituric acid reactive substances (TBARS) and Lohmann chicken egg cholesterol) but there was a difference in feed intake. The uronic acid extracted from S. crassifolium has not been able to increase the production and quality of Lohmann chicken eggs.Keywords: lohmann chicken, quality of eggs, Sargassum crassifolium, uronic acid